(untitled) (Journal of Pharmaceutical Negative Results, 2022)
The Internet of Things (IoT) is a network of internet-enabled accessory containing integrated sensors and actuators for external communication. The numeral of devices attached to the Internet is rising at a fast rate because of their extensive uses in several fields, like health care farming, sports, and patient safety. The IoT is a concept that considers the persistent presence of wireless, cable, interactive, communicable and collaborative things and objects and that allows new services to achieve common goals, such as diagnostic of symptoms of disease, treatment, a patient cure. The internet offers various healthcare applications from remote monitoring to intelligent sensors and the integration of medical devices. Healthcare IoT can also increase patient involvement and happiness by allowing patients to spend more time with their physicians. A promising technology is now made of IoT-enabled wearable sensors that allow continuous wireless monitoring of critical physiological variables. The focus here was on developing a combination product that was the development of smart metered-dose inhalers, one of the most visible areas of digital pharmaceutical involvement by studying related work. This digital technology was developed in order to improve lung diseases like asthma and COPD and to improve the efficiency of the prescribed media. These monitoring devices connect themselves to the inhaler of your user and should ideally be able to monitor compliance, record the accuracy of every dose, retain data, and not allow access to data to download to the computer for dosing regimen by doctors.